The role of electrostatic interactions in the Streptococcus thermophilus adhesion on human erythrocytes in media with different 2:1 electrolyte concentration - Гордієнко, О. І.; Баранник, М. О.; Гордієнко, Є. О. (Biophysical Bulletin, 1970)
In the two-stage sorption model at the first stage is mostly reversible attachment, while at the second irreversible stage molecular and cellular adhesion processes take place. An important factor, influencing the adhesion processes, is physical-chemical characteristics of the medium, in particular, the presence of divalent cations therein. The aim of this work is to assess the role of electrostatic component of the intercellular interactions in media with different 2:1 electrolyte concentration at the first reversible stage of adhesion and probability of further occurrence of specific binding. Electrostatic interactions play a decisive role in intercellular adhesion process. The obtained experimental results and theoretical calculations of the electrostatic interaction parameters once again confirmed the acceptability of a two-stage model of sorption and DLVO theory to describe a cell-cell adhesion.